2017
DOI: 10.1530/ec-17-0220
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thimerosal on thyroid hormones metabolism in rats

Abstract: Mercury seems to exert an inhibitory effect on deiodinases, but there are few studies using Thimerosal (TM) as the mercury source. We aimed to elucidate the effect of TM on thyroid hormones peripheral metabolism. Adult Wistar female rats received 0.25 µg or 250 µg TM/100 g BW, IM, twice a week, for a month. We evaluated serum total T3 and T4, D1 activity using 125I-rT3 as tracer, and D2 activity using 125I-T4. NADPH oxidase activity was measured by Amplex-red/HRP method and mRNA levels by real time PCR. Serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Mercury affects the function of the endocrine system by decreasing its hormone-receptor binding ability ( Iavicoli et al, 2009 ). Previous studies have reported that thimerosal critically affected the metabolism of thyroid hormones in rats by reducing the activity of deiodinase D1 and D2 in tissues by binding directly to the selenium of catalytic site ( Pantaleao et al, 2017 ). It has been experimentally proved that mercury causes damage to male gonads and disrupts steroidogenesis and spermatogenesis ( Zhu et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mercury affects the function of the endocrine system by decreasing its hormone-receptor binding ability ( Iavicoli et al, 2009 ). Previous studies have reported that thimerosal critically affected the metabolism of thyroid hormones in rats by reducing the activity of deiodinase D1 and D2 in tissues by binding directly to the selenium of catalytic site ( Pantaleao et al, 2017 ). It has been experimentally proved that mercury causes damage to male gonads and disrupts steroidogenesis and spermatogenesis ( Zhu et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%